Peningkatan pemahaman konsep perjuangan mempertahankan kemerdekaan indonesia melalui model two stay two stray pada siswa kelas v sekolah dasar - Saputri, Nia; Mahfud, Hasan; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2019)
The aim of this research is to increase conceptual understanding of Indonesia independence struggle by applying Two Stay Two Stray (TSTS) model. This research is Classroom Action Research (CAR) with two cycles. Subjects of the research are fifth grade students and teacher at SD N Kartasura 07, totalling 19 students. Data collection techniques that being used are interview, observe, test and documentation with data analysis of contents validity, source tringaluation and technique triangulation. Data analysis used is the interactive  analysis model by Miles-Huberman’s technique. The first cycle resulting in a percentage of 52,63% in classical and the result of second cycle with the percentage of 89,47% in classical. The conclusion is the result of understanding the conceptual of Indonesia independence struggle have increased through the Two Stay Two Stray model in fifth grade students of SD N Kartasura 07 in the academic year of 2018/2019.